Effects of HIV exposure on anemia and vitamin D nutritional status in children aged 6–24 months: a hospital-based cross-sectional study - Huixia Li; Shan Yuan; Minghui Liao; Sanfeng Tan; Jianfei Zheng; Lijia Wan; Ying Tu; Min Yang; Jie Gao (Scientific Reports)
Abstract There is little research on anemia and vitamin D deficiency in HIV-exposed uninfected (HEU) children. This study was aimed to describe and compare the prevalence of anemia and vitamin D inadequacy in HEU children and HIV-unexposed uninfected (HUU) children, and to examine the associations of HIV exposure with anemia and vitamin D inadequacy. This was a hospital-based descriptive cross-sectional study nested within the Prevention of Mother-to-Child Transmission (PMTCT) of HIV program in Hunan Province during July and September 2022. The HEU children aged 6 to 24 months were recruited from the PMTCT outpatient clinics located in five Municipal Maternal and Child Health Care Hospitals. The HUU children were recruited from routine child health examination clinics in the same five Hospitals. Questionnaires about children’s characteristics and maternal gestational conditions were collected from children’s caregivers, and blood samples were collected from all children. Descriptive statistics, Chi-square test, non-parametric rank sum test, and logistic regression were used for analysis. The study population included 336 HEU children and 334 HUU children. The overall prevalence of anemia in the HEU and HUU children was 10.4% and 8.1%, respectively. The median hemoglobin concentrations were 120 (115–126) g/L in the HEU children and 122 (116–129) g/L in the HUU children. Neither prevalence of anemia nor hemoglobin concentration was significantly different between the two groups (P > 0.05). The prevalence of vitamin D inadequacy in the HEU children (19.6% for deficiency and 25.0% for insufficiency) was significantly higher than that of the HUU children (11.4% for deficiency and 16.2% for insufficiency) (P < 0.001). The median 25(OH)D concentration in the HEU children was significantly lower than that of the HUU children (23.80 (13.50–34.08) vs. 32.08 (18.60–39.32) ng/ml) (P < 0.001). HIV exposure in HEU children was significantly associated with an increased risk of vitamin D deficiency (adjusted OR (AOR) 1.72, 95% CI: 1.13–2.61) and vitamin D insufficiency (AOR 1.53, 95% CI: 1.01–2.34), but not with anemia (AOR 0.80, 95% CI: 0.32–2.01). The PMTCT program shall strengthen vitamin D supplementation in HEU children and caregivers shall appropriately extend the outdoor activity time of HEU children to reduce the occurrence of vitamin D inadequacy.